Evaluation of emissions characteristics in dual-fuel RCCI engines operating with diesel-bioethanol and biodiesel-bioethanol fuel combinations - Hishammudin Afifi, Huspi; Teoh, Yew Heng; Heoy, Geok How (Elsevier B.V., 2026)
This study presents a comparative evaluation of Diesel–Bioethanol and Biodiesel–Bioethanol dual-fuel Reactivity Controlled Compression Ignition (RCCI) operations using a custom-built, low-cost common-rail injection system with Arduino-based electronic control. The aim is to identify the optimum start-of-injection (SOI) strategy for reducing emissions in biofuel-fueled RCCI engines, contributing to the development of sustainable and affordable low-emission combustion systems. Experiments were performed under 30 % exhaust gas recirculation (EGR) across a range of SOI timings, with emphasis on nitrogen oxides (NOx), carbon monoxide (CO), and unburned hydrocarbons (HC). Results reveal distinct combustion behaviors between the two configurations: Biodiesel–Bioethanol exhibited earlier combustion initiation due to biodiesel’s higher cetane number, achieving lower CO and HC but higher NOx emissions, while Diesel–Bioethanol offered reduced NOx with slightly higher CO levels. Optimal combustion efficiency and lowest emissions were obtained at mid-advanced SOI (15–25 °CA BTDC) for both fuel sets. This work provides new experimental evidence on how fuel reactivity and injection phasing interact in biofuel-based RCCI engines and demonstrates the practical feasibility of low-cost control systems for achieving stable, clean combustion. The findings contribute to the ongoing pursuit of renewable, high-efficiency propulsion technologies aligned with sustainable development goals.